Prevalence and association between alcohol, tobacco, and COVID-19: a study from a tribal predominant district in eastern India - Narasimha, Venkata Lakshmi; Nath, Santanu; Alam, Benazir; Kumari, Bipasa; Kumari, Pooja; Kumari, Shalini; Kaur, Jagdish; Varshney, Saurabh (Frontiers in Public Health, 2024)
Introduction Alcohol and tobacco use has been proposed to significantly affect COVID-19 outcomes. The study aimed to estimate the prevalence of alcohol and tobacco use among COVID-19-positive patients and compare it with the general population prevalence rates. It also aimed to assess and determine the association between the severity of COVID-19 illness and the complications with alcohol and tobacco use. Method For this, a cross-sectional, retrospective, telephone-based study was conducted using a structured questionnaire among COVID-19 diagnosed patients in the district of Deoghar of the Indian state of Jharkhand. A multinomial logistic regression is done to determine the association. Results Among 1,425 patients interviewed, tobacco and alcohol were used by 22.31 and 9.96%, significantly more than the prevalence of tobacco (Z = 4.9485, p < 0.00001) and alcohol use (Z = 7.118, p < 0.00001), respectively, in the district (tobacco-11.7% and alcohol-4.8%). In a regression model, patients with co-morbidity had higher odds of severe [3.34 (1.99–5.62)] and moderate [2.95 (1.97–4.41)] COVID-19. Young [0.12 (0.04–0.38)] and middle-aged individuals [0.23 (0.13–0.4)], people below the poverty line 0.28 (0.11–0.69) are at lower odds of severe COVID-19. Tobacco users [1.58 (1.16–2.14)], alcohol users [1.53 (1.03–2.28)], incomplete vaccination [3.24 (1.49–7.01)], and patients with comorbidity [3.6 (2.79–4.68)] were found to have higher odds of post-COVID-19 complications. Discussion People with COVID-19 in our study population had significantly higher tobacco and alcohol use compared to the general population. Tobacco and alcohol use significantly increases the risk of post-COVID-19 complications. The study highlights the need for addiction treatment services to prevent complications during future pandemics.